The Levinson Theory in the detection of spelling errors among dyslexic children - Wan Mohammad, Wan Muna Ruzanna; Subramaniam, Vijayaletchumy (Sara Publishing Academy, 2013)
In 2004, Malaysian Education Ministry (KPM) had begun its “Pilot Program of Dyslexia-Specific Learning Problems”, and currently in 2012 there are already 49 primary schools with 86 dyslexia classes throughout Malaysia. This study focuses on the detection of spelling errors in the Malay Language essay-writing done by dyslexic children all across Terengganu, Malaysia. This spelling error detection was centralized on the Levinson Theory, 1994. This theory has shown seven aspects of errors in the writing done by dyslexic children, namely errors in terms of (i) elimination, (ii) transfer, (iii) insertion, (iv) replacement, (v) reversal, (vi) wild guess, and (vii) condensation. This study was done on eight dyslexic children aged 10 years old registered with the Society Welfare Department, Terengganu and all of them were adopted as the sample of the study. The study findings have demonstrated that elimination, replacement and wild guess were among the most committed by the subjects. Meanwhile, in terms of transfer, reversal and condensation, they were the lowest committed by the subjects. The study outcome had given priority to the instructors of the dyslexic class, for them to make some improvements on the teaching and learning strategies in facilitating the process of mastering the spelling for the subject of study. The variety of therapies used to promote spelling mastery can be used as a consolidation in learning and to strengthen exercises both in school and outside class hours.